Young Children Bet on Their Numerical Skills: Metacognition in the Numerical Domain. (September 2014) - Vo, Vy A.; Li, Rosa; Kornell, Nate; Pouget, Alexandre; Cantlon, Jessica F.
Metacognition, the ability to assess one's own knowledge, has been targeted as a critical learning mechanism in mathematics education. Yet the early childhood origins of metacognition have proven difficult to study. Using a novel nonverbal task and a comprehensive set of metacognitive measures, we provided the strongest evidence to date that young children are metacognitive. We showed that children as young as 5 years made metacognitive "bets" on their numerical discriminations in a wagering task. However, contrary to previous reports from adults, our results showed that children's metacognition is domain specific: Their metacognition in the numerical domain was unrelated to their metacognition in another domain (emotion discrimination). Moreover, children's metacognitive ability in only the numerical domain predicted their school-based mathematics knowledge. The data provide novel evidence that metacognition is a fundamental, domain-dependent cognitive ability in children. The findings have implications for theories of uncertainty and reveal new avenues for training metacognition in children.